Challenges and Opportunities in Implementing Tuberculosis Prevention Therapy in Developing Countries: A Scoping Review - Brigadini Ayuning Putri; Martha Irene Kartasurya; Bagoes Widjanarko (Green Publisher Indonesia, 2025)
Tuberculosis Prevention Therapy (TPT) is an effort to prevent tuberculosis (TB) in people who have close contact with TB-positive patients. However, the challenges and opportunities in implementing TPT have not been fully explored. This study aims to examine the challenges and opportunities in implementing TPT within health services in developing countries. A systematic search was conducted using electronic databases (Scopus, PubMed, Science Direct, ProQuest) for literature published between 2015 and 2025. Following the PRISMA-ScR guidelines, 10 articles from various developing countries were included in the final analysis. Studies available in English with quantitative or qualitative designs and free full-text access were selected. The findings reveal that limited access to health services, inadequate health resources, insufficient knowledge, and adverse social environments constitute the primary challenges to implementation. Conversely, stakeholder support and strategic development of health services present significant opportunities to improve TPT uptake and completion. These insights provide evidence-based guidance for policymakers and healthcare practitioners to formulate targeted strategies that address implementation barriers and leverage existing opportunities to reduce the TB burden in resource-limited settings.